Penentuan Pelarut Terbaik pada Ekstraksi Tanin Kulit Kayu Akasia dan Pengaruhnya Sebagai Inhibitor Laju Korosi pada Baja Karbon - Ayu Ratna Permanasari; Tri Reksa Saputra; Aprillia Nurul’ Aina; Salma Liska (Jurnal Teknik Kimia dan Lingkungan, 2020)
Carbon steel in industrial equipment which direct contact with the environment will eventually be corroded. The rate of corrosion could be slowed by organic inhibitors of tannin compounds contained from acacia trees. Tannins were obtained from the extraction process using methanol and ethanol. The aims of this research were to determine the best solvent in the extraction process of acacia bark based on the largest tannin content and to study the effect of tannin as a corrosion inhibitor on carbon steel in the corrosive media through weight reduction methods. The extraction process used maceration at room temperature for two hours with a solid:solvent ratio of 1:10. The solvents were ethanol and methanol. The extract was evaporated in a rotary evaporator at 50 oC, 100 mbar became a paste form. Bark extract was added as an inhibitor in 0.5 M H2SO4 corrosive media; HCl 0.5 M; sea ​​water, and tap water with the addition of inhibitor concentrations of 4%, 6% and 8% (w /v). Immersion was carried out for 12, 24, 36, 48, 60 and 72 hours. Methanol was a better solvent than ethanol with a yield of 4.57% and tannin concentration of 2.768 ppm. Tannin in acacia bark extract is suitable to be used as a corrosion inhibitor in acidic media such as H2SO4 0.5 M and 0.5 M HCl with the highest efficiency gains are 81.20% and 53.06%, respectively.